2022
DOI: 10.3390/ma15062237
|View full text |Cite
|
Sign up to set email alerts
|

Improving Energy Harvesting from Bridge Vibration Excited by Moving Vehicles with a Bi-Stable Harvester

Abstract: To monitor the health status of the bridge, many sensors are needed to be mounted on it. Converting bridge vibration energy to electrical energy is considered as a potential solution to the problem of providing reliable electric power to these sensors. The objective of this work is to present an operable strategy for improving the electric energy output of a piezoelectric energy harvester installed on a bridge by introducing bi-stable characteristics. A bi-stable harvester is proposed. By adjusting the tip and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The linear system configuration of the device has a natural frequency of 14.5 Hz; in the monostable case, the frequency varies and at the speed of 1.07 m/s, its frequency is 4.9 Hz. Moreover, in another bi-stable configuration of the harvester (Zhou et al, 2022) the power density of 680 W/m 3 is reported at a rolling mass speed of 2.5 m/s.…”
Section: Behs Tested In-lab Environment Onlymentioning
confidence: 94%
“…The linear system configuration of the device has a natural frequency of 14.5 Hz; in the monostable case, the frequency varies and at the speed of 1.07 m/s, its frequency is 4.9 Hz. Moreover, in another bi-stable configuration of the harvester (Zhou et al, 2022) the power density of 680 W/m 3 is reported at a rolling mass speed of 2.5 m/s.…”
Section: Behs Tested In-lab Environment Onlymentioning
confidence: 94%
“…Nonlinear energy harvesting technologies aim to develop power-autonomous devices in various sectors, such as aeronautics [ 13 , 14 ], infrastructure [ 15 ], medicine [ 16 ] and wearables [ 17 ], as parts of IoT networks. The electromechanical concept of multi-stable vibration may be based on two major mechanism categories: (i) electromagnetic forces applied via the opposite polarization of magnets located on the vibrating piezoelectric structure and the supporting device [ 18 , 19 ] or (ii) base excitation and axial compressive forces acting on a piezoelectric structure up to post-buckling [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%